Overview of Community Diseases in the Pomalaa Sub-district which is in the Mining area of PT. Dewi Jaya 2021 - Wahyuni Chivansa, Firsta; Saafi, La Ode; Harun, Aziz; Hardianti, Hardianti (Waluya The International Science of Health Journal, 2022)
Introduction: Pomala sub-district, which is a mining area, is an area that is very vulnerable to being affected by several diseases. This study aims to describe some of the dominant diseases/diseases suffered by the community around the mining area of ​​Pt. Dewi Jaya who is a partner of Pt. Antam in 2021. Method: This type of research is descriptive by taking secondary data at the Pomala Health Center in 2021. The sample in this study was 183 people from the total population. Result: The results showed that several diseases found in the mining area community were ARI, Hypertension, Dyspepsia, Dermatitis, Myalgia, DM, Asthma, and Vulnus Laceratum. This is certainly related to several factors such as environmental pollution in this case the air that has been polluted so it has an impact on the health of the people of the mining area. Conclusion: The conclusion is a picture of the disease that exists in the community in the mining area of ​​Pt. Dewi Jaya is ARI, Hypertension, Dyspepsia, Dermatitis, Myalgia, DM, Asthma, and VulnusLaceratum.